Determination of bisphosphonates anti-resorptive properties based on three forms of ceramic materials: Sorption and release process evaluation - Monika Zielińska; Ewa Chmielewska; Tomasz Buchwald; Adam Voelkel; Paweł Kafarski (Elsevier, 2021)
There is a strong need to search for more effective compounds with bone anti-resorptive properties, which will cause fewer complications than commonly used bisphosphonates. To achieve this goal, it is necessary to search for new techniques to characterize the interactions between bone and drug. By studying their interaction with hydroxyapatite (HA), this study used three forms of ceramic materials, two of which are bone-stimulating materials, to assess the suitability of new active substances with anti-resorptive properties. In this study, three methods based on HA in loose form, polycaprolactone/HA (a polymer-ceramic materials containing HA), and polymer-ceramic monolithic in-needle extraction (MINE) device (a polymer inert skeleton), respectively, were used. The affinity of risedronate (a standard compound) and sixteen aminomethylenebisphosphonates (new compounds with potential antiresorptive properties) to HA was defined according to the above-mentioned methods. Ten monolithic materials based on 2-hydroxyethyl methacrylate/ethylene dimethacrylate are prepared and studied, of which one was selected for more-detailed further research. Simulated body fluids containing bisphosphonates were passed through the MINE device. In this way, sorption-desorption of bisphosphonates was evaluated using this MINE device. The paper presents the advantages and disadvantages of each technique and its suitability for assessing new active substances. All three methods allow for the selection of several compounds with potentially higher anti-resorptive properties than risedronate, in hope that it reflects their higher bone affinity and release ability.